Computing Impulse Response of Room Acoustics Using the Ray-Tracing Method in Time Domain - Adil ALPKOCAK; Malik Kemal SIS (Archives of Acoustics, 2013)
This paper proposes a new approach for calculating the impulse response of room acoustics. Impulse response provides unique characterization of any discrete linear-time invariant (LTI) systems. We assume that the room is a linear time-invariant system and the impulse response is calculated simply by sending a Dirac Impulse into the system as input and getting the response from the output. Then, the output of the system is represented as a sum of time-shifted weighted impulse responses. Both mathematical justifications for the proposed method and results from simulation software developed to evaluate the proposed approach are presented in detail.